Water and Society Changing Perceptions of Societal and Historical Development - Tvedt, Terje (Bloomsbury Academic, 2021)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Despite the central importance that water has held for civilizations both ancient and modern, its social significance has made surprisingly little impact on our contemporary understanding of human history and development. Dominant interpretations of the relationship between society and nature have remained water blind. In Water and Society historian and leading water expert Terje Tvedt argues for a change that acknowledges the significant role played by water in societal development. Reflecting his expertise as a geographer, historian and a political scientist, and drawing on his wide experience of water issues around the world, Terje Tvedt s Water and Society provides a long overdue reappraisal of the relationship between water and society, one that gives water its rightful place as central to any true understanding of human history and development."